Arriving at a social equity orientation on workplace domestic violence policy in Australia. (2nd October 2022) - Ellicott, Susan G.
ABSTRACT: This article examines Australian Government workplace domestic violence policy as a workplace equality and gender equality policy. Drawing on Baird's typology of policy orientations and systematic process analysis of documents and elite interviews with 43 key informants, this article contributes a process theory of how and why workplace domestic violence policy developed in Australia. It finds non-traditional actors (anti-domestic violence advocates, trade union members and researchers) led traditional actors (components of the state, trade unions and employer parties) towards orientations and mechanisms on this policy post-2010 likely to enhance the social equity of employees experiencing domestic violence. Significant to non-traditional actor effectiveness on this was their lived expertise and experience on domestic violence, and trade union support.